2021
DOI: 10.21203/rs.3.rs-513630/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Platelet-rich Plasma Combined With Core Decompression Bone Grafting for Osteonecrosis of Femoral Head: A Meta-Analysis

Abstract: Objective: Core decompression bone grafting usually is used hip-preserving approach for osteonecrosis of femoral head (ONFH). Platelet-rich plasma (PRP) is an adjuvant therapy, combined with core decompression bone grafting for ONFH. However, it remains controversial. Therefore, its efficacy was systematically evaluated and meta-analysis in this study.Methods: Literature on core decompression bone grafting for ONFH was retrieved in CNKI, Wan Fang, PubMed, Embase, Cochrane Library and Web of Science from incept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Harris hip score (HHS). A total of 13 studies [24,26,27,[29][30][31][32][33][34][35][36][37][38] with 809 participants reported HHS between the treatment groups and control groups. Among the 13 studies, 7 studies [26,27,[31][32][33][34][35] reported HHS at 3 months postoperatively, 9 studies [26,27,[29][30][31][32][33][34][35] reported HHS at 6 months postoperatively, 9 studies [26,27,31,32,[34][35][36][37][38] reported HHS at 12 months postoperatively, and 3 studies [25,30,32] reported HHS at � 24 months postoperatively.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Harris hip score (HHS). A total of 13 studies [24,26,27,[29][30][31][32][33][34][35][36][37][38] with 809 participants reported HHS between the treatment groups and control groups. Among the 13 studies, 7 studies [26,27,[31][32][33][34][35] reported HHS at 3 months postoperatively, 9 studies [26,27,[29][30][31][32][33][34][35] reported HHS at 6 months postoperatively, 9 studies [26,27,31,32,[34][35][36][37][38] reported HHS at 12 months postoperatively, and 3 studies [25,30,32] reported HHS at � 24 months postoperatively.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…A total of 13 studies [24,26,27,[29][30][31][32][33][34][35][36][37][38] with 809 participants reported HHS between the treatment groups and control groups. Among the 13 studies, 7 studies [26,27,[31][32][33][34][35] reported HHS at 3 months postoperatively, 9 studies [26,27,[29][30][31][32][33][34][35] reported HHS at 6 months postoperatively, 9 studies [26,27,31,32,[34][35][36][37][38] reported HHS at 12 months postoperatively, and 3 studies [25,30,32] reported HHS at � 24 months postoperatively. Meta-analysis was performed on the last follow-up time points, and at different followup time points postoperatively (3-, 6-, 12-, and � 24-month follow-ups) when those were reported by the respective studies.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 3 more Smart Citations